HUMANITARIAN DA'WAH MESSAGES ON INSTAGRAM: CONTENT ANALYSIS OF @salimafillah_official FOR ACEH TAMIANG RELIEF - Wulan, Amanda; Azhar, Anang Anas (Jurnal Al-Ijtimaiyyah, 2026)
This study aims to analyse humanitarian da'wah messages on Instagram in the context of fundraising for the Aceh Tamiang disaster through the @salimafillah_official account. The increasing use of social media as a platform for humanitarian campaigns has expanded the function of da'wah beyond mobilising public donations to strengthening spiritual awareness and social solidarity. This study addresses three research questions concerning the variation of humanitarian da'wah messages, the consistency of message delivery, and the dominance of fundraising documentation compared with substantive da'wah messages. A descriptive qualitative approach employing content analysis was applied to 2 Instagram posts, including captions, images, and videos uploaded during the fundraising campaign. Data were collected through documentation of Instagram content and a literature review, and analysed using thematic content analysis. The findings reveal that humanitarian da'wah messages are consistently communicated through persuasive narratives integrating emotional, rational, and religious appeals. However, the variation of messages remains limited and tends to be repetitive. In addition, the content is predominantly focused on documenting fundraising activities rather than providing deeper spiritual guidance for disaster victims. Nevertheless, reflective narratives promoting empathy, compassion, and public participation remain evident throughout the campaign. The study concludes that Instagram-based humanitarian da'wah functions as an effective medium for moral communication and social mobilisation, although greater diversity and depth of da'wah messages are needed to optimise both humanitarian and spiritual objectives.